Targeting the ubiquitin-proteasome system: four-membered ring inhibitors of proteasome - Heydarpour Klidsar, Maryam (2022)
Tese de mestrado, Química Farmacêutica e Terapêutica, 2019, Universidade de Lisboa, Faculdade de Farmácia.